Implementasi Problem Based Learning Dalam Mata Pelajaran Al – Islam Dan Kemuhammadiyahan Di SMA Muhammadiyah Pontren Imam Syuhodo - Shofiyah, Luthfi Nurul; Inayati, Nurul Latifatul (Jayapangus Press, 2025)
This study aims to study three aspects, namely: Planning, Implementation, and Evaluation of Problem Based Learning model learning to improve students' critical thinking skills in Al-Islam and Muhammadiyah subjects in grades X, XI, XII at Muhammadiyah Pontren Imam Syuhodo High School. This study uses qualitative research methods. Data sources are obtained from primary and secondary data. The researcher obtained primary data directly from al-Islam and Muhammadiyah teachers. Secondary data sources come from previous journals and information provided by al-Islam and Muhammadiyah teachers. Data was collected through observation, interviews, and documentation. Direct interviews with al-Islam and Muhammadiyah experts then conduct observations and documentation. The data were validated by triangulation. The results of the research show that the educational planning has been adjusted to the Muhammadiyah curriculum. To improve students' critical thinking skills, the facilitator uses the Problem Based Learning model at the learning implementation stage. This model includes problem-oriented to learners, organizing learners, guidance in individual and group investigations, creating and presenting works, and analyzing the evaluation of the problem-solving process. For the evaluation stage, the Al-Islam and Muhammadiyah teachers did not use observation sheets to assess the students' activeness. On the other hand, the Al-Islam and Muhammadiyah teachers conduct assessments by assigning assignments, which are then discussed by students. Thus, the students of SMA Muhammadiyah Pontren Imam Syuhodo showed an improvement in their critical thinking skills during the learning process which was based on problems.